Alzheimer disease in post-menopausal women: Intervene in the critical window period - Nayer Jamshed; Fouzia Firdaus Ozair; Praveen Aggarwal; Meera Ekka (Wolters Kluwer Medknow Publications, 2014)
Alzheimer disease (AD) is a crippling neurodegenerative disorder. It is more common in females after menopause. Estrogen probably has a protective role in cognitive decline. Large amount of research has been carried out to see the benefits of hormone replacement therapy with regards to Alzheimer still its neuroprotective effect is not established. Recent studies suggest a reduced risk of AD and improved cognitive functioning of post-menopausal women who used 17 β-estradiol in the critical period. Use of 17 β-estradiol in young and healthy post-menopausal women yields the maximum benefit when the neurons are intact or neuronal stress has just started. Hence intervention in the critical period is key in the prevention or delay of AD in post-menopausal women.